ANALYSIS OF APPLICATION USE OF PESTICIDES AND PESTICIDE RESIDUE ON VEGETABLES IN SAMBIREJO VILLAGE - Agus Widada; Defi Ermayendri; Yusmidiarti Yusmidiarti; Rosalina Rina Bathari (Proceeding B-ICON, 2022)
The use of chemical-based pesticides has been proven to increase farmers' production, so that almost all farmers use pesticides in all farming. Excessive use will cause pesticide residues in vegetables to be high. The purpose of this research was to determine the use of pesticides in terms of dosage, accuracy of pesticides, the time span of spraying with harvests and pesticide residues in vegetables. This research used a qualitative approach to see the behavior of farmers in the application of pesticides, data collection methods by conducting interviews and FGDs. Respondents in this research were 50 vegetable farmers randomly taken. The FGD was attended by 10 people consisting of the head of the farmer group and the Agricultural Extension Officer while the vegetable samples were taken 4 which were selected based on the highest frequency sprayed. The results of this research were 70% of farmers applied pesticides according to the dosage, 50% of farmers applied pesticides based on pest observations, 18% according to the distance of the last spraying with the harvest time with a time of more than 7 days, and the pesticide residues on chlorpiripos leeks exceeded the threshold value with a concentration of 0.051 mg/kg or exceeding NAV 76.47%, while the pesticide residue type of parathion with a concentration of 0.039 exceeds the NAV of 8.3%. It is supposed that farmers can apply the right target rules, the right dosage, the right time, the right way and the right type so that the risk of pesticide residues on vegetables can be minimized